Populist tactics and populist rhetoric in political parties of Post-Soviet Russia - Yuri Korgunuyuk (Universidade Federal de Goiás, 2010)
The article of Yu. Korguniuk (Russia) is devoted to various appearances of populism in tactics and rhetoric of political parties in post-Soviet Russia (since 1990). The author discusses these appearances in activities both of political parties which may be called populist without a shadow of doubt, and parties which use populist tactics and populist rhetoric but cannot be considered populist in the full sense of the word. To his opinion, populism in post-Soviet Russia has some features similar to Latin American populism and some which distinguish it from the latter. The common characteristics are charismatic leadership, political personalism, priority of leadership over institutions, adherence to national development concepts and anti-globalization movement. The difference lies in the interpretation of 'anti-imperialism': the Russian populism is anti-American and anti-Western but not anti-imperialist in general. Russian populists are, as a rule, extreme Russian imperialists and, to a certain degree, nationalists. The Russian populism also may be called statist and paternalistic: there is almost no difference between left (socialist) and right (nationalist and conservative) populisms in Russia. Besides, the author argues that many traditional ideologies - such as communism and nationalism - are, in fact, varieties of 'state populism' in today's Russia. He concludes that populism have embraced the whole Russian political spectrum, including even those sectors which have always positioned themselves as anti-populist.